On-Sky Demonstration of Low-Order Wavefront Sensing and Control with Focal Plane Phase Mask Coronagraphs. (4th January 2016) - Singh, Garima; Lozi, Julien; Guyon, Olivier; Baudoz, Pierre; Jovanovic, Nemanja; Martinache, Frantz; Kudo, Tomoyuki; Serabyn, Eugene; Kuhn, Jonas
Abstract: The ability to characterize exoplanets by spectroscopy of their atmospheres requires direct imaging techniques to isolate planet signal from the bright stellar glare. One of the limitations with the direct detection of exoplanets, either with ground- or space-based coronagraphs, is pointing errors and other low-order wavefront aberrations. The coronagraphic detection sensitivity at the diffraction limit therefore depends on how well low-order aberrations upstream of the focal plane mask are corrected. To prevent starlight leakage at the inner working angle of a phase mask coronagraph, we have introduced a Lyot-based low-order wavefront sensor (LLOWFS), which senses aberrations using the rejected starlight diffracted at the Lyot plane. In this article, we present the implementation, testing, and results of LLOWFS on the Subaru Coronagraphic Extreme Adaptive Optics system (SCExAO) at the Subaru Telescope. We have controlled 35 Zernike modes of a H-band vector vortex coronagraph in the laboratory and 10 Zernike modes on-sky with an integrator control law. We demonstrated a closed-loop pointing residual of 0.02 mas in the laboratory and 0.15 mas on-sky for data sampled using the minimal 2-s exposure time of the science camera. We have also integrated the LLOWFS in the visible high-order control loop of SCExAO, which in closed-loop operation has validated the correction of the noncommon path pointing errors between the infrared science channel and the visible wavefront sensing channel with pointing residual of 0.23 mas on-sky.